Institutional care during wartime and the extent of potential support for migrants arriving from Ukraine in the light of the actions of education offices in Poland - Agnieszka Szplit; Anita Garbat; Renata Miszczuk (Studia z Teorii Wychowania)
The aim of this paper is to analyse the extent of institutional care for Ukrainian immigrants offered by education offices and to show its evolution over time. The research material consisted of entries on the websites of 16 education offices, from February 24, 2022, to February 24, 2024. The research method used is “netnography”. This research identifies several areas of action of the education offices: official, educational, methodological, economic, psychological-pedagogical, health-related, and local. The authors refer their findings to a 4-phase care model by Joan Tronto's theory. Over the second year of the war, an evident evolution of institutional care can be observed.